2012
DOI: 10.3109/08990220.2012.686937
|View full text |Cite
|
Sign up to set email alerts
|

Perception of fluids with diverse rheology applied to the underarm versus forearm skin

Abstract: Little is known about the tactile-perceptual structure of fluids. Therefore, ten fluids with diverse, characterized rheologies were rated by 16 females, on 27 sensory attributes (e.g., "slippery") and 14 emotional attributes (e.g., "enjoyable") via five-point categorical scales. Fluids were assessed against the volar forearm and underarm, sites that commonly experience contact with fluids during the use of personal care products. Application of fluids was either by the participant to their own body ("self-appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…The first two emotional factors matched very well those from prior work in social psychology, which suggested that any emotional experience is embodied with certain amounts of three independent qualities, namely Pleasure, Arousal and Dominance [27][28][29][30]. Unlike the sensory experience of touch, the factors describing the emotional experience of touch appear quite similar for the tactile experience of dry and fluid stimuli [20,21]. The emotional experience of Dominance has not emerged in these studies, perhaps because Dominance is only of consequence in interactions between, or assessments of, other humans (perception of facial expression, [31], perception of body posture, [32]).…”
Section: Perceptual Dimensions and Skin Care Productssupporting
confidence: 72%
See 3 more Smart Citations
“…The first two emotional factors matched very well those from prior work in social psychology, which suggested that any emotional experience is embodied with certain amounts of three independent qualities, namely Pleasure, Arousal and Dominance [27][28][29][30]. Unlike the sensory experience of touch, the factors describing the emotional experience of touch appear quite similar for the tactile experience of dry and fluid stimuli [20,21]. The emotional experience of Dominance has not emerged in these studies, perhaps because Dominance is only of consequence in interactions between, or assessments of, other humans (perception of facial expression, [31], perception of body posture, [32]).…”
Section: Perceptual Dimensions and Skin Care Productssupporting
confidence: 72%
“…Our suggestion was that words describing the overall sensory experience of touch (i.e., semantic-perceptual space) fall along three orthogonal axes, approximating Rough-Smooth, Dry-Wet and Hot-Cold (Figure 1), but when actual dry, textured stimuli were assessed using these words (i.e., using the TPT), orthogonal factors emerged describing, in decreasing order of importance, Roughness, Slip, Firmness and Pile. The subsequent extension of this work to the perception of skin care products [21] suggested five orthogonal sensory factors approximating Wetness, Texture, Slickness, Silkiness and Viscosity. Water is, of course, a fluid that is of paramount importance for humans, and the primacy of the wetness factor may reflect water's critical role in our lives.…”
Section: Perceptual Dimensions and Skin Care Productsmentioning
confidence: 97%
See 2 more Smart Citations
“…roughness in exfoliating scrubs or heat in lipolytic creams) (Guest et al, 2013). Sensory characteristics commonly evaluated during product application include absorbency, cloudiness, freshness, greasiness, oiliness, roughness, silkiness, smoothness, spreadability, stickiness, thickness, tingling, viscosity, waxiness, warming, cooling, melting, wetness, tautness (ASTM, 2011;Guest, Mehrabyan, Essick, Hopkinson, & McGlone, 2012;Meilgaard, Civille, & Carr, 2000, chap. 11;Parente, Ares, & Manzoni, 2010;Stone & Sidel, 1986;Wortel & Wiechers, 2000).…”
Section: Introductionmentioning
confidence: 98%